Two-Phase Flow in Refrigeration Systems - Gu, Junjie; Wang, Shujun; Gan, Zhongxue; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This critical volume presents recent developments from the authors' extensive research programs on two-phase flow in refrigeration systems. This book covers advanced mass and heat transfer and vapor compression refrigeration systems and shows how the performance of an automotive air-conditioning system is affected through results obtained experimentally and theoretically, specifically with consideration of two-phase flow and oil concentration. This book also: ·         Illustrates criticality of two-phase flow and oil concentration of refrigeration systems to performance of refrigeration systems ·         Presents new understanding of two-phase flow aimed at engineers designing efficient refrigeration systems ·         Provides experimentally and theoretically derived results on performance of automotive air-conditioning systems ·         Includes abundant field and test data from commercial-scale refrigeration components ·         Features over 100 illustrations Two-Phase Flow in Refrigeration Systems is ideal for university postgraduate students as a textbook,  researchers and professors as an academic reference book, and by engineers and designers as a handbook.
Introduction -- Experimental Facility for Two-Phase Flow Measurement -- Properties of Refrigerant, Oil and Their Mixture -- Two-Phase Flow in Accumulator -- Two-Phase Flow in Compressor -- Two-Phase Flow in Adiabatic Capillary Tube for R-134a Cycles -- Two-Phase Flow in Non-Adiabatic Capillary Tube for CO2 Cycles -- Two-Phase Flow in Internal Heat Exchangers -- Two-Phase Flow and System Performance -- Appendix -- Index.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Fluid mechanics; Engineering Thermodynamics, Heat and Mass Transfer; Thermodynamics; Engineering Fluid Dynamics